Pengaruh Pembelajaran Tari Berbasis Multimedia Terhadap Kreatifitas Seni Tari Siswa SMP PAB 2 Helvetia Medan - CICI SUCISKA NINGSIH (Gesture: Jurnal Seni Tari, 2017)
This study aims to determine the effect of multimedia-based learning to creative dance dance school students PAB 2 Helvetia Medan Semester 1, T.A 2016/2017.In this discussion uses the theories related to the topic of research that influence theory, learning, teaching methods, instructional media, multimedia, audio, visual, audiovisual, internet, learning dance, dance, and creativity.The method used is quantitative research methods .Instrumen used to collect data is the t test. T tests were used to determine whether the two variables have a significant contribution or not. The population in this study were junior high school students PAB 2 Helvetia Medan Semester 1 T.A 2016/2017. Of this population taken sample of students of class VIII SMP PAB 2 Helvetia Medan totaling 35 students. This study used the class pretest and posttest.From the data acquisition is known that the ability of students to learning dance before using multimedia is enough In the category with an average value and standard deviation = 64.35 = 9.40. The ability of the students after using multimedia to be in both categories with an average value of 72.95 and standard deviation = 9.76. Based on calculations normality test showed that the data pretest and posttest data is normally distributed. The test results prove that the homogeneity of the sample is derived from a homogeneous population. Hypothesis testing is done by using the test "t" The results of test calculations "t" obtained t greater than ttable which is 3.69> 2.00, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the multimedia-based learning dance a significant effect on creativity dance school students PAB 2 Helvetia Medan. Keywords: Multimedia-Based Learning Dance, Creativity Dance of Art